Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1371/journal.pone.0135058
|View full text |Cite
|
Sign up to set email alerts
|

Bisulfite Conversion of DNA: Performance Comparison of Different Kits and Methylation Quantitation of Epigenetic Biomarkers that Have the Potential to Be Used in Non-Invasive Prenatal Testing

Abstract: IntroductionEpigenetic alterations, including DNA methylation, play an important role in the regulation of gene expression. Several methods exist for evaluating DNA methylation, but bisulfite sequencing remains the gold standard by which base-pair resolution of CpG methylation is achieved. The challenge of the method is that the desired outcome (conversion of unmethylated cytosines) positively correlates with the undesired side effects (DNA degradation and inappropriate conversion), thus several commercial kit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 53 publications
4
48
0
Order By: Relevance
“…Some controls (commercial or artificially methylated DNA fragments) are available to estimate this inappropriate conversion rate, but, to our knowledge, they are not systematically used in WGBS experiments. Some studies using such controls have shown that the inappropriate conversion rate (% of methylated cytosines converted to uracils) ranges from 0.09% to 6.1% depending on the kit and protocol used [56][57][58].…”
Section: Methimpute Facilitates Insights Into Bisulfite Conversion Ratesmentioning
confidence: 99%
“…Some controls (commercial or artificially methylated DNA fragments) are available to estimate this inappropriate conversion rate, but, to our knowledge, they are not systematically used in WGBS experiments. Some studies using such controls have shown that the inappropriate conversion rate (% of methylated cytosines converted to uracils) ranges from 0.09% to 6.1% depending on the kit and protocol used [56][57][58].…”
Section: Methimpute Facilitates Insights Into Bisulfite Conversion Ratesmentioning
confidence: 99%
“…However, the low pH and high temperature in this reaction can lead to incomplete or inappropriate bisulfite conversion as well as DNA degradation, resulting in over or underestimation of DNA methylation (Olova et al, 2018;Ji et al, 2014;Genereux et al, 2008). Recently, different commercial bisulfite conversion kits, applied to various DNA sources with high and low molecular weigh (HMW/LMW), have been comprehensively evaluated for their DNA recovery and bisulfite conversion efficiencies (Holmes et al, 2014;Leontiou et al, 2015;Ørntoft et al, 2017;Tierling et al, 2018). In these performance evaluations, highly sensitive detection methods such as quantitative and digital PCR (qPCR, dPCR) were used to amplify different target regions in genomic DNA (HMW-DNA) or in circulating cell-free DNA (LMW-DNA) (Ørntoft et al, 2017;Tierling et al, 2018;Kint et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…One example is bisulfite sequencing, which comes in a number of variations (whole genome, reduced representation, target sequencing of specific gene regions) and has been shown to provide high resolution of the methylation landscape within genomes (Metzger & Schulte, 2016). However, this technique is expensive, can result in excessive DNA degradation, and requires a related reference genome for the species of interest, something that is still lacking for most non-model organisms (Leontiou et al 2015; Metzger & Schulte, 2016).…”
Section: Introductionmentioning
confidence: 99%